Visualisation of the Motion Trajectory for Rolling Motion of Snake Robots using Virtual Chassis and Simplified Kinematics Motion Model. Issue 32 (2016) - Gilani, Cid; Chen, XiaoQi; Pretty, Chris; Koike, Carla
Abstract: The ability to visualise the motion trajectory of snake robots is important for path-planning and control and thus, their effectiveness in operation. This paper focuses on visualising the motion trajectory of snake robots in a rolling gait. Rolling is a relatively simple gait, but not all snake robots roll in a straight line, tending to deviate in the direction towards the centre of mass of snake robots. A kinematics motion model is used to capture the differential motion of each module of the snake robot between time-steps with the assumption that the underside of each module interacts with flat ground as a wheel. The virtual chassis approach then allows us to separate the internal body shape of the snake robot from the world frame and simplify modelling of the overall motion. Results obtained from modelling and experimentation are presented in this paper to validate the accuracy of the predicted motion trajectory.